2015
DOI: 10.1177/0193945915610083
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Hypothalamic Stimulation Reduces Hyperalgesia Through Spinally Descending Orexin-A Neurons in Neuropathic Pain

Abstract: No evidence to date shows that lateral hypothalamic (LH) stimulation produces orexin-A mediated antinociception in the spinal cord dorsal horn (SCDH) in a model of neuropathic pain. We conducted experiments to examine the effect of orexin-A-mediated LH stimulation in female rats with chronic constriction injury (CCI) on thermal hyperalgesia. Rats receiving carbachol into the LH demonstrated antinociception on both the left CCI and right non-ligated paws (p < 0.05). Rats were given carbachol in the LH followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Many previous studies report links between the ZI and chronic pain 19,20. The ZI is a GABAergic nucleus located in the ventral thalamus, which is a subdivision of the diencephalon, and most ZI neurons are GABAergic 21,22.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies report links between the ZI and chronic pain 19,20. The ZI is a GABAergic nucleus located in the ventral thalamus, which is a subdivision of the diencephalon, and most ZI neurons are GABAergic 21,22.…”
Section: Introductionmentioning
confidence: 99%
“…Noradrenergic neurons in the A7 area increase their firing rates when exposed to substance P [21], microinjection of substance P in the A7 area produces antinociception [6], and microinjection of the neurokinin1 receptor antagonist, L-703,606, into the A7 area reduces LH-induced antinociception [13]. Orexins-containing neurons are prevalent in the LH and are known to play a role in nociceptive modulation either by a direct connection to the spinal cord dorsal horn or at supraspinal levels [22,23,24]. LH orexin-containing neurons project to the parabrachial area [25], but no behavioral studies have been done demonstrating an LH to A7 orexins connection.…”
Section: Discussionmentioning
confidence: 99%
“…This study focused on the actions of LH neurons only in the noradrenergic descending modulatory system. As mentioned earlier, LH stimulation also activates orexin–containing neurons in the LH that project directly to the dorsal horn [24,25], and possibly met-enkephalin [27] and glutamate neurons [28]. Similarly, LH innervation of the A7 area may activate non- noradrenergic neurons, including GABA and glycine neurons that are known to exist near the A7 cells [7,21].…”
Section: Discussionmentioning
confidence: 99%
“…26,60,61 Central sensitization may also result from direct chemotoxic damage [62][63][64] and/or dysfunction of the CNS descending pain-modulating pathways. [65][66][67][68] Very few studies have reported chemotherapy effects on descending pain-modulating pathways; however, emerging evidence suggests that analgesia through the descending pain-modulating pathway, particularly involving the lateral hypothalamus and orexinergic system, may be key in combatting CIPN pain. [65][66][67][68] The longer CIPN goes unmanaged, the more central sensitization progresses; painful CIPN then becomes chronic.…”
Section: Chronic Painful Cipnmentioning
confidence: 99%